2020
DOI: 10.3892/etm.2020.9309
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 promotes pulmonary artery endothelial cell proliferation by targeting the Akt signaling pathway

Abstract: Pulmonary arterial hypertension (PAH) is a disease characterized by a progressive increase in pulmonary vascular resistance and obliterative pulmonary vascular remodeling; however, the pathogenesis of the disease is not completely understood. Sirtuin 1 (SIRT1) is a histone deacetylase involved in cell survival and metabolism. The present study explored the potential role of SIRT1 in human pulmonary arterial endothelial cells (HPAECs) under hypoxic conditions. In vitro HPAECs were cultured and exposed to hypoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…In addition, we showed that Sirt1 knockdown also attenuated the enhanced phosphorylation of EGFR, ERK1/2 and AKT in VSMC from SHR and suggest the role of Sirt1 in the activation of these signaling molecules implicated in the overexpression of Giα proteins and hyperproliferation. Furthermore, our results showing that knockdown of Sirt1 also inhibited basal EGFR and AKT phosphorylation in VSMC from WKY rats are in accordance with the studies of other investigators who showed that inhibition of Sirt1 by a specific inhibitor EX-527, also attenuated the phosphorylation of AKT in pulmonary artery endothelial cells [51] and phosphorylation of EGFR as well as PDGFR in rat renal interstitial fibroblasts [52]. However, it should be noted that the inhibition of basal EGFR and AKT phosphorylation by Sirt1 knockdown did not have any effect on the basal proliferation of VSMC from WKY rats.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we showed that Sirt1 knockdown also attenuated the enhanced phosphorylation of EGFR, ERK1/2 and AKT in VSMC from SHR and suggest the role of Sirt1 in the activation of these signaling molecules implicated in the overexpression of Giα proteins and hyperproliferation. Furthermore, our results showing that knockdown of Sirt1 also inhibited basal EGFR and AKT phosphorylation in VSMC from WKY rats are in accordance with the studies of other investigators who showed that inhibition of Sirt1 by a specific inhibitor EX-527, also attenuated the phosphorylation of AKT in pulmonary artery endothelial cells [51] and phosphorylation of EGFR as well as PDGFR in rat renal interstitial fibroblasts [52]. However, it should be noted that the inhibition of basal EGFR and AKT phosphorylation by Sirt1 knockdown did not have any effect on the basal proliferation of VSMC from WKY rats.…”
Section: Discussionsupporting
confidence: 93%
“…Acetylation and deacetylation balance owing to Sirt1 inactivation alters pulmonary hypertension pathogenesis [ 60 ]. When it comes to pulmonary hypertension, Sirt1 up-regulation initiates the Akt signaling pathway to facilitate hypoxia-elicited proliferation in human pulmonary artery endothelial cells and curb their apoptosis [ 61 ]. Moreover, Sirt1 activators can also curb NF-κB-mediated inflammatory reactions, thus exhibiting regulatory functions in VSMC disorders [ 62 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 is a class III histone deacetylase that functions as an example of an NAD + ‐dependent histone deacetylase. SIRT1 is crucial for several biological processes, including cell differentiation, apoptosis and embryonic development (Xi et al, 2020). AKT1 is the downstream molecule of SIRT1, which has a significant impact on the control of protein synthesis, cell survival and proliferation (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%